Florigen-Encoding Genes of Day-Neutral and Photoperiod-Sensitive Maize Are Regulated by Different Chromatin Modifications at the Floral Transition - Mascheretti, Iride (Plant Physiol, 2015)
The activity of the maize (Zea mays) florigen gene ZEA CENTRORADIALIS8 (ZCN8) is associated with the floral transition in both day-neutral temperate maize and short-day (SD)-requiring tropical maize. We analyzed transcription and chromatin modifications at the ZCN8 locus and its nearly identical paralog ZCN7 during the floral transition. This analysis was performed with day-neutral maize (Zea mays ssp. mays), where flowering is promoted almost exclusively via the autonomous pathway through the activity of the regulatory gene indeterminate1 (id1), and tropical teosinte (Zea mays ssp. parviglumis) under floral inductive and noninductive photoperiods. Comparison of ZCN7/ZCN8 histone modification profiles in immature leaves of nonflowering id1 mutants and teosinte grown under floral inhibitory photoperiods reveals that both id1 floral inductive activity and SD-mediated induction result in histone modification patterns that are compatible with the formation of transcriptionally competent chromatin environments. Specific histone modifications are maintained during leaf development and may represent a chromatin signature that favors the production of processed ZCN7/ZCN8 messenger RNA in florigen-producing mature leaf. However, whereas id1 function promotes histone H3 hyperacetylation, SD induction is associated with increased histone H3 dimethylation and trimethylation at lysine-4. In addition, id1 and SD differently affect the production of ZCN7/ZCN8 antisense transcript. These observations suggest that distinct mechanisms distinguish florigen regulation in response to autonomous and photoperiod pathways. Finally, the identical expression and histone modification profiles of ZCN7 and ZCN8 in response to floral induction suggest that ZCN7 may represent a second maize florigen.